Experiences of healthcare providers during the coronavirus pandemic and its impact on them: protocol for a mixed-methods systematic review - Xiaofeng Li; Yan Su; Na Xu; AiLi Lv; TianZi Li; Mei Huang (BMJ Open)
Introduction Frontline healthcare providers are redeployed to areas outside their clinical expertise and assigned high-loading workload to address the surge of patients with each coronavirus outbreak. Their importance in crisis is not in doubt. However, they experienced considerable physical distress and psychological stressors, even leading to psychological illness and infection in this environment. There is an urgent need to accurately, comprehensively and objectively understand their experiences, perceptions and current situation of burnout, post-traumatic stress disorder (PTSD), anxiety, depression, insomnia and coronavirus infection. Therefore, this protocol is to conduct a mixed-methods systematic review to summarise the evidence on the experiences of healthcare providers and impacts of the coronavirus on their psychological status and infection during the pandemics.Methods Published studies on experience, perspective, impact, burnout, PTSD, anxiety, depression, insomnia, and infection of healthcare providers with SARS, Middle East respiratory syndrome and COVID-19, and written in English and Chinese will be accepted. Databases (MEDLINE, EMBASE, CENTRAL, Web of Science, PubMed, Psychology Information, WanFang and SinoMed) from inception until 30 July 2020 will be searched. Two reviewers will select, screen, extract data and assess the risk of bias independently. Risk of bias of results will be using the Mixed-Methods Appraisal Tool. Using a convergent integrated approach on qualitative/quantitative studies, we will synthesise qualitative and quantitative data separately. The incidence and number of cases about burnout, PTSD, anxiety, depression, insomnia and coronavirus infection among medical staff will be extracted. Then we will transform quantitative data to synthesise narrative findings. This protocol will be reported per the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines.Ethics and dissemination Ethical assessment is not required due to the nature of the proposed systematic review. Findings of our research will be disseminated at conferences related to this field and through publication in peer-reviewed journals.PROSPERO registration number CRD42020198506.